Prevalence and determinants of selected cardio-metabolic risk factors among people living with HIV/AIDS and receiving care in the South West Regional Hospitals of Cameroon: a cross-sectional study - Ngu, R; Choukem, S; Dimala, C; Ngu, J; Monekosso, G (BioMed Central, 2018)
Objective Metabolic disorders and cardiovascular risk factors are not routinely assessed in the care of HIV patients in developing countries, known to have the highest disease burden. We described the prevalence and factors associated with major cardio-metabolic risk factors (obesity, diabetes and hypertension) in HIV/AIDS patients. Results The prevalence of diabetes, hypertension and obesity were 11.3% (95% CI 8.10–15.43), 24.8% (95% CI 20.1–30.0) and 14.5% (95% CI 11.1–19.3) respectively. Central obesity and high alcohol intake were the factors significantly associated with diabetes mellitus, while central obesity and overweight/obesity were significantly associated with having hypertension. Short duration of antiretroviral therapy was the significant predisposing factor for obesity. On multivariate analyses, the only association observed was between central obesity and diabetes (Adjusted OR 2.52, 95% CI 1.01–6.30, P = 0.048). Conclusively, DM, HTN and obesity are highly prevalent in HIV/AIDS patients in the SWR hospitals of Cameroon, with that of DM and obesity being higher than that seen in the general population while that of HTN equaling that of the general population. Awareness of these data among clinicians involved in the management of these patients should be emphasized.